PREFERRED STRATEGIES USED BY PEKANBARU SENIOR HIGH SCHOOL STUDENTS TO LEARN PRODUCTIVE SKILLS OF ENGLISH - Fakhri Ras (Jurnal Pendidikan, 2013)
The objective of this study is to investigate how Pekanbaru senior high school students learnproductive language skills (speaking and writing). One of the definitions of language learning strategies isdefined by Oxford (1990b). She states that language learning strategies are specific actions taken by thelearner to make learning easier, faster, more enjoyable, and more efficient. The needed data were collectedby interviewing 10 selected students from five ethnic groups (Malay, Minang, Javanese, Batak, and Chinese)at various senior high schools in Pekanbaru. The respondents were asked to answer the following question:If you are asked to increase the productive language skills, what do you do? Inter-rater reliability wasused to judge the answers of related respondents in the interview by the qualified inter-raters-that aremaster’s degree in TEFL. The inter-raters modified the respondents’ responses in casual English intoacceptable written English without changing the concept of the expression. The highest frequency hasbeen acknowledged. There are a lot of strategies identified as the most-preferred strategies employed bythe respondents to increase the productive skills. The use of these strategies can be grouped into once-mentioned, twice-mentioned, and more than twice-mentioned. Examples of strategies mentioned morethan twice for improving speaking skills, preparing as much vocabulary as possible (four times); and forimproving writing skill, the strategy of writing procedurally (three times). Suggestions for further study arethose the successful learners, less successful learners, and gifted learners should also be taken into accountas crucial factors to investigate in the near future.Keywords: The Preferred Strategies, Senior High School, Productive Skill